Evaluation of the Sustainability based on integral resilience of Homegardens in Totonacapan, Mexico - Rajabopal, Indumathi (Universidad Autónoma Chapingo, 2021)
Traditional agroecosystems, including homegardens (HGs), face various natural and anthropogenic alterations derived from adverse modifications in the current environment, economic, and sociocultural conditions. Consequently, the resilience and sustainability of these evidenced in some rural communities in Mexico are put at risk. This study aimed to evaluate the current degree of integral resilience of homegardens in the study area to determine their degree of sustainability. A sample of 12 homegardens was selected in the Totonac community of Santiago Ecatlan, Puebla. Data were collected from thirty members of different age groups during June 2018-July 2019. A conceptual framework of resilience was developed based on the hypothesis that the higher the magnitude of agrodiversity, the higher the integral resilience of homegardens. A methodology was adapted to operationalize the framework in which the resilience index was elaborated using both qualitative and quantitative methods, and multi-criteria analysis of FlowSort was carried out to evaluate the sustainability of the HGs based on their resilience category. The results show that orchards no° H1, H4, H5, and H2 registered the highest resilience index (RI). Garden H10 registered the lowest RI, without differentiating from H8 and H9. The FlowSort analysis showed that H1, H2, H4, and H5 orchards belong to the high resilience category, while the rest belong to the medium resilience category. Finally, the orchards that belong to the high resilience category were evaluated as potentially sustainable. To conclude, homegardens with high agrobiodiversity, management and conservation capacity, monetary gains, and organizational capacity contribute to increasing ecological, economic, and cultural resilience in the face of adverse challenges. Thus, the more significant the transmission, conservation, and improvement of agrodiversity associated with homegardens and the degree of appreciation for it by current and future generations, the greater the integral resilience and sustainability of Totonacapan homegardens.
Tesis (Doctorado en Agricultura Multifuncional para el Desarrollo Sostenible)
Keywords: Agrodiversity; Agroforestry; Biocultural heritage; Incluive development; Multifunctional agriculture; Traditional knowledge